2020
DOI: 10.1002/jnr.24746
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional interventions to improve neurophysiological impairments following traumatic brain injury: A systematic review

Abstract: Traumatic brain injury (TBI) accounts for significant global health burden. Effects of TBI can become chronic even following mild injury. There is a need to develop effective therapies to attenuate the damaging effects of TBI and improve recovery outcomes. This literature review using a priori criteria (PROSPERO; CRD42018100623) summarized 43 studies between January 1998 and July 2019 that investigated nutritional interventions (NUT) delivered with the objective of altering neurophysiological (NP) outcomes fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 136 publications
(419 reference statements)
0
10
0
Order By: Relevance
“…(positive) effect, vs. only 19% reported a negative interaction (6). Nutrition interventions for both prevention and treatment of TBI symptomatologies have been reported (24)(25)(26). While several therapies, including vitamins (B 2 , B 3 , B 6 , B 9 , C, D, and E) and nutrients (arginine, carnitine, magnesium, omega-3 fatty acids, resveratrol, selenium, and zinc) have demonstrated efficacy in preclinical studies, using rats and mice, but investigations of polytherapy treatments have not been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…(positive) effect, vs. only 19% reported a negative interaction (6). Nutrition interventions for both prevention and treatment of TBI symptomatologies have been reported (24)(25)(26). While several therapies, including vitamins (B 2 , B 3 , B 6 , B 9 , C, D, and E) and nutrients (arginine, carnitine, magnesium, omega-3 fatty acids, resveratrol, selenium, and zinc) have demonstrated efficacy in preclinical studies, using rats and mice, but investigations of polytherapy treatments have not been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Diets rich in red meat, saturated and trans fats, refined sugars, and carbohydrates are associated with neuroinflammation, while neuroprotective and anti-inflammatory effects are linked to diets high in unsaturated, polyunsaturated, and monounsaturated fats, as well as ketogenic and Mediterranean diets, and intermittent fasting [139]. The effects on anti-neuroinflammatory (ANI) diets on TBI outcomes are being worked out in both preclinical [140] and clinical studies [108,141]. Specific supplements have been extensive studied, most notably the use of omega oils [142][143][144].…”
Section: Dietary Changesmentioning
confidence: 99%
“…It no longer seems so clear that sTBI‐induced damage can only be treated within a few hours after the trauma, and the possibility of a longer therapeutic window of time for pharmacological intervention is in discussion 7 . For reduction of secondary damage, anti‐oxidants, branched‐chain amino acids, and ω‐3 polyunsaturated fatty acids have shown promising pre‐clinical results 8 . However, pharmacological research has not yet identified a “gold standard” to prevent secondary brain damage.…”
Section: Introductionmentioning
confidence: 99%
“… 7 For reduction of secondary damage, anti‐oxidants, branched‐chain amino acids, and ω‐3 polyunsaturated fatty acids have shown promising pre‐clinical results. 8 However, pharmacological research has not yet identified a “gold standard” to prevent secondary brain damage. Although there are promising data from animal studies, the only positive findings in retrospective 9 , 10 and prospective “real life” clinical trials 11 , 12 were achieved with Citicoline and Cerebrolysin.…”
Section: Introductionmentioning
confidence: 99%